Design and evaluation of a paediatric neurology data management system in hospitals of Iran. (2nd August 2019) - Esmaeilzadeh, Fatemeh; Samad-Soltani, Taha; Barzegar, Mohammad; Rezaei-Hachesu, Peyman
Provision of high quality care for paediatric neurological diseases require timely and perfect collection, storage, and analysis of data pertaining to these patients. In this applied-developmental study, the features and minimum dataset of the registration system were determined by reviewing the scientific literature and consulting with experts on the subject. The unified modelling language was used to develop the conceptual model of the system. The conceptual diagram was evaluated with the verification and validation method. Results of the evaluation showed that about 75% of syntax rules, 62% of semantic rules, 80% of aesthetic rules are observed. Comparison of the system developed based on the designed conceptual model with 240 previous studies showed its excellent quality in terms of attractiveness, efficiency, dependability, and novelty and its good quality in terms of perspicuity and stimulation. The use of conceptual design and evaluation methods led to development of a more efficient system.